Análisis del principio de celeridad en la tramitación de la acción de protección en el contexto de la pandemia en la ciudad de Ibarra, provincia de Imbabura, Ecuador - Erazo Delgado, Anderson Fabián (2024)
This study addresses the analysis of the principle of celerity in the processing of the protection action in the context of the COVID-19 pandemic in the city of Ibarra, province of Imbabura, Ecuador. Through an analysis of legal documents, academic literature and data from the Sistema Automated System for Judicial Proceedings, we explore how the health crisis has been developing the application of the principle of speed in the judicial system. The study focuses on evaluating judicial practice during the pandemic, identifying challenges and proposing improvements. Qualitative methods are employed, including documentary analysis and interviews with judges, lawyers and experts, complemented by examination of relevant court cases during the pandemic period. The findings indicate a controversy between theory and practice in the application of the principle of celerity. Despite clear guidelines in Ecuadorian legislation, the reality shows variations in its implementation, exacerbated by the pandemic. Interviews and analysis of specific cases reveal efforts to maintain procedural celerity through virtual hearings and efficient digitization, but challenges related to case overload and technological adaptation persist. In response, strategies are suggested to improve the efficiency of the judicial system, including technological modernization, training in digital tools, revision of procedural deadlines, strengthening of the electronic notification system and continuous evaluation. Finally, these recommendations seek to improve the alignment between judicial practice and legal regulations, strengthening confidence in the justice system and ensuring effective protection of rights in crisis situations.